BASIC PRINCIPLES OF HYDROSTATIC LEVELLING - Pospíšil, Jiří; Dandoš, Rostislav (GeoScience Engineering, 2018)
The paper aims to introduce the distribution, history and the basic physical principles hydrostatic leveling. The principle of this method is based on the known law of connected vessels filled with fluid. Well, known equipment is surface water level, the height of the surface is deducted on a millimeter scale. There are currently used devices that allow deducting with an accuracy of 0.01 mm. Keywords: levelling, height, hydrostatic pressure https://doi.org/10.2478/gse-2018-0008